A Rare Case in Turkey: Cocaine-induced Multifocal Leukoencephalopathy - ERDİL, ESRA; TUNÇ, HANDENUR (TURKISH NEUROLOGICAL SOC, 2020)
Use of cocaine can cause neorologic disorders such as hemorrhagic and ischemic cerebrovascular disease, seizure, neuropsychiatric complications, movement disorders, cerebral vasculitis, reversible cerebral vasoconstriction syndrome, and multifocal leukoencephalopathy. Among them, multifocal inflammatory leukoencephalopathy occurs rarely and is found to be related with a cocaine adulterant, levamisole. In this report, a case of cocaine/levamisole-related multifocal inflammatory leukoencephalopathy appearing with clinical features of catatonia is presented. A 34-year-old female patient was evaluated with symptoms of loss of contact and abnormal behaviour at the emergency department. She was living in Austria and had used cocaine three weeks before admission to hospital. A neurologic examination revealed increased speech latency, echolalia, and poor cooperation. Cranial magnetic resonance imaging showed bilateral fluid-attenuated inversion recovery and T2 hyperintense round-oval shaped lesions with patchy restricted diffusion and heterogenous contrast enhancement in subcortical periventricular white matter. Cranial imaging findings mimicked demyelinating diseases in this patient. Probable use of levamisole-adulterated cocaine, by enhancing immune response, caused levamisole-related multifocal leukoencephalopathy. The patient was started on pulse methylprednisolone treatment. At the request of the patient, on the sixth day of the treatment, she was transferred abroad and further follow-up could not be made. It is known that the use of levamisole, either for medical purpose or as an illegal substance, triggers multifocal leukoencephalopathy by means of complex immune mechanisms. The clinical presentation, radiologic impression, and histological findings of this condition are compatible with demyelinating diseases. Given the increased incidence use of cocaine with its most common adulterant levamisole, recognition and clinical management of its neurologic complications is crucial.
Keywords: Levamisole; cocaine; leukoencephalopathy; magnetic resonance; INFLAMMATORY LEUKOENCEPHALOPATHY; LEVAMISOLE; ADULTERANTS